A methodology for producing knowledge in public safety through data and information visualization resources - Gomes, Gabriel Ângelo da Silva; Pinto, Adilson Luiz; Meneses, Nicodemos Coutinho de (Advanced Notes in Information Science, 2023)
The National Criminal Information System contains millions of criminal records. However, despite aggregating a large amount of data, it is clear that the System mainly works as a data repository or source only for consulting criminal records. Thus, this research aims to propose a methodology for analyzing Sinic data linked to business intelligence and graph generator tools so that the product obtained is of high value for criminal investigation and police intelligence. This is a case study involving the analysis of the theft of the Central Bank in Fortaleza - CE (Bacen - CE). It was found that solutions such as dashboards and graphs in social network analysis enhance the visualization of data and information, especially when investigating complex networks, thus maximizing the user's cognitive power. Before presenting it, a necessary contextualization of theoretical supports related to Information Science visualization resources follows.